Die Uniekheid van Getal en Ruimte as Grondslag vir Besinning oor die Elementêre Grondbegrippe in die Wiskunde - Wessels, Dirk C. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
The question: What is mathematics?, can only be answered when the aspects of number and space are analysed in their uniqueness and mutual interrelationship. The supporters of the Philosophy of the Cosmonomic Idea have made a huge contribution to a detailed analysis of the meaning of cosmic time as well as a responsible recognition of the time intuition of the human being. This has enabled them to give a sound explanation of the meaning of the potential and complete infinite and to stear away from arithmeticism in the views of what number is. The fundamental difference beween discrete quantity and continuous extendedness is stressed – the latter defines the spatial aspect. An explication of the subject-object relationship shed some light on the relationship between points and lines, the meaning of time-order for the spatial aspect and the differences between analytical, Euclidean and non-Euclidean geometries. The way is now open to investigate the nature of analogies and metaphors in our attempt to identify and analyse the elementary basic concepts in mathematics.